(untitled) (Revista Venezolana de Salud Pública, 2019)
The present essay aims to arrive at the recognition of the achievements in the recovery of the capacities in the search of the autonomy of the body as a foundation in the practice of health promotion in the Las Delicias Foundation (FLD); Community project located in the rural area of ​​Caserío Las Ánimas, Yaritagua District of Yaracuy state in Venezuela. The text is structured in three parts: The introduction, which briefly describes the scenario where the practice of PS develops and sets out the fundamental categories that will be analyzed. The development, where, supported by the documentary review, a set of arguments that allow an approach to the understanding of the body-territory ontological category as a fundamental element in the study of health promotion are analyzed and synthesized. As well as sustaining how the human being needs to recover autonomy over his body and to activate the available resources to develop healthy life projects. Subsequently, we managed to explain how the FLD has internally organized its health promotion practices, based on the implementation of three lines of work, to ensure that its users achieve the recovery of their body’s autonomy. Finally, the conclusion where they are stated for discussion, the achievements obtained in the recovery of the abilities to face and overcome the hegemonic discourse that prevents taking control of your body. With these results, the Foundation is committing itself to a superior value that is the promotion of life, through the dignification of the human person.